EGFR Inhibition in Glioma Cells Modulates Rho Signaling to Inhibit Cell Motility and Invasion and Cooperates with Temozolomide to Reduce Cell Growth - Ramis, Guillem; Thomàs-Moyà, Elena; Fernández de Mattos, Silvia; Rodríguez, José; Villalonga, Priam (PLOS ONE, 2012)
Enforced EGFR activation upon gene amplification and/or mutation is a common hallmark of malignant glioma. Small molecule EGFR tyrosine kinase inhibitors, such as erlotinib (Tarceva), have shown some activity in a subset of glioma patients in recent trials, although the reported data on the cellular basis of glioma cell responsiveness to these compounds have been contradictory. Here we have used a panel of human glioma cell lines, including cells with amplified or mutant EGFR, to further characterize the cellular effects of EGFR inhibition with erlotinib. Dose-response and cellular growth assays indicate that erlotinib reduces cell proliferation in all tested cell lines without inducing cytotoxic effects. Flow cytometric analyses confirm that EGFR inhibition does not induce apoptosis in glioma cells, leading to cell cycle arrest in G1. Interestingly, erlotinib also prevents spontaneous multicellular tumour spheroid growth in U87MG cells and cooperates with sub-optimal doses of temozolomide (TMZ) to reduce multicellular tumour spheroid growth. This cooperation appears to be schedule-dependent, since pre-treatment with erlotinib protects against TMZ-induced cytotoxicity whereas concomitant treatment results in a cooperative effect. Cell cycle arrest in erlotinib-treated cells is associated with an inhibition of ERK and Akt signaling, resulting in cyclin D1 downregulation, an increase in p27kip1 levels and pRB hypophosphorylation. Interestingly, EGFR inhibition also perturbs Rho GTPase signaling and cellular morphology, leading to Rho/ROCK-dependent formation of actin stress fibres and the inhibition of glioma cell motility and invasion.